Table of Content - - (Journal of Humanities & Social Sciences, 2025)
:Table of Content• General social aspects in Baghdad through the book 'Nishwar AI-Muhadara' by AI-TanukhiAsst-Lecturer. Ahmad Taleb Malouh, Asst-Prof. Hamid Karimipour• The Maturation of Developmental Concepts in Islamic Thought and Its Impact on Guiding Human Action: The Model of Justice from Theological Belief to Moral EducationDr. Fazry Hamza• Ibn Rushd and his intellectual and philosophical role: A study of his intellectual influences in Europe and the Western opinion of himAsst-Lecturer. Zainab Nasser Abdul-Hussein Al-Azirjawi, Asst-Prof. Nour Al-Din Nemati• The Role of Digital Communication in Promoting Civic Participation – Moroccan platform I share a model –Dr. Filali S. Zineb• The Impact of Social and Cultural Factors on the Effectiveness of Tourism Management  in Major Projects: A Human-Centered PerspectiveEng. Ashraf Fawzy Al-Jindi• Reception Dynamics and the Theme of Human Fall in Absurdist Literature: An Interactive Reading of Three Short Stories by Friedrich Dürrenmatt"Dr. Hani Khamis Hamad• An Exploration of Morpho-Syntactic Elements of Block Language in Journalistic DiscourseMr. Omar Hazim Yaseen
Keywords: The Journal of Human and Social Sciences